mTOR hyperactivity and RICTOR amplification as targets for personalized treatments in malignancies - Dániel Sztankovics; Dorottya Moldvai; Gábor Petővári; Titanilla Dankó; Fatime Szalai; Risa Miyaura; Viktória Varga; Noémi Nagy; Gergő Papp; Judit Pápay; Ildikó Krencz; Anna Sebestyén (Frontiers Media S.A., 2024)
The increasing knowledge of molecular alterations in malignancies, including mutations and regulatory failures in the mTOR (mechanistic target of rapamycin) signaling pathway, highlights the importance of mTOR hyperactivity as a validated target in common and rare malignancies. This review summarises recent findings on the characterization and prognostic role of mTOR kinase complexes (mTORC1 and mTORC2) activity regarding differences in their function, structure, regulatory mechanisms, and inhibitor sensitivity. We have recently identified new tumor types with RICTOR (rapamycin-insensitive companion of mTOR) amplification and associated mTORC2 hyperactivity as useful potential targets for developing targeted therapies in lung cancer and other newly described malignancies. The activity of mTOR complexes is recommended to be assessed and considered in cancers before mTOR inhibitor therapy, as current first-generation mTOR inhibitors (rapamycin and analogs) can be ineffective in the presence of mTORC2 hyperactivity. We have introduced and proposed a marker panel to determine tissue characteristics of mTOR activity in biopsy specimens, patient materials, and cell lines. Ongoing phase trials of new inhibitors and combination therapies are promising in advanced-stage patients selected by genetic alterations, molecular markers, and/or protein expression changes in the mTOR signaling pathway. Hopefully, the summarized results, our findings, and the suggested characterization of mTOR activity will support therapeutic decisions.